Diseño de una plataforma de cargue y descargue de isotanques con capacidad de hasta 100 litros (2022)
At present, the economic situation of the country has been in a great decline, which makes it impossible to renew and acquire new vehicles from the automotive fleet oriented to industrial work, which forces companies and owners of these types of vehicles to perform reinventing and/or modifying to accomplish assigned tasks. In this work, the mechanical design of a platform or device for loading and unloading isotanks weighing up to one ton was carried out, for a truck-type vehicle with a capacity of up to 4 tons, this was done in order to improve the process. of loading and unloading in areas where there is a lack of cranes or traditional forklifts, in order to be able to achieve better efficiency and avoid any risk for the work personnel in charge of these isotanks, everything that will be done will be based and It will comply with the parameters established by the Ministry of Transit and Transportation. For the cost analysis we will look for th